Pendekatan Andragogi dalam Pembelajaran Bahasa Arab - Setyawan, Cahya Edi (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2017)
The term Andragogy does not seem so familiar to educators and teachers. Educators and teachers are more familiar with the term Pedagogy, because the term is used in education. If it refers to the meaning of the term Pedagogy is the education of children, while Andragogy is an adult education. Andragogy began to be known today by educational activists, this is because the emergence of the problem of education at this time is the number of adults who started learning material that the material should have been learned in childhood. The problem is how to adapt the educational methods used to adult-like adults. In learning Arabic there is a problem when adults begin to study the material that should be the same as madrasah tsanawiyah or aliyah. Teachers should treat like adults in the learning process, therefore adults as students should be treated appropriately. Teachers are no longer the main actors or as learning centers but teachers are only facilitators and students become learning centers. The learning process focuses on providing assistance to the participants to understand what is the focus of attention and problems. Arabic learning using Andragogi approach focuses on aspects of student self-concept in learning objectives, previous learning experiences about Arabic, readiness to learn new Arabic material with new environmental conditions, and orientation or ideals towards learning Arabic. Arabic learning model using Andragogi approach include the method of humanistic, constructiveness, and problem solving.